Productive and economic efficiency of carrot intercropped with cowpea-vegetable resulting from green manure and different spatial arrangements - Favacho, Fernando; Lima, Jailma Suerda; Bezerra Neto, Francisco; Silva, Josimar; Barros Júnior, Aurélio (Revista Ciência Agronômica, 2016)
The aim of this study was to evaluate the agro-economic efficiency of intercropping carrot with cowpea-vegetable in relation to the amounts of biomass of Calotropis procera (Ait.) R.Br. (known locally as flor-de-seda) incorporated into the soil, and to different spatial arrangements. The study was carried out under field conditions from August to November of 2014, at the Experimental Farm ‘Rafael Fernandes’ of the Rural Federal University of the Semi-Arid (RFUSA), in Mossoró, in the State of Rio Grande do Norte, Brazil. The experimental design was a randomised complete blocks in a 4 x 3 factorial, consisting of a combination of four different amounts of flor-de-seda biomass incorporated into the soil (20, 35, 50 and 65 t ha-1 of dry matter) and three spatial arrangements for the crop rows (2 x 2, 3 x 3 and 4 x 4). The carrot and cowpea cultivars used were ꞌBrasíliaꞌ and ꞌBRS Itaimꞌ. The characteristics under evaluation in the carrot were total, commercial and classified root production (scrap, short, medium and long). For the cowpea-vegetable, the following were evaluated: number, productivity and dry matter weight of green pods, number of grains per pod, 100-grain weight and yield of green grains. The agro-economic efficiency indices evaluated in the intercropping were: land equivalent ratio for the system and partial land equivalent ratios for the crops, monetary advantage and modified monetary advantage. The greatest agro-economic efficiency with the intercrop system was recorded in the biomass amount of 30 t ha-1 flor-de-seda. The 2 x 2 spatial arrangement resulted in greater system efficiency. The use of flor-de-seda as green manure is economically viable for the farmer when intercrop carrot with cowpea-vegetable.